2023
DOI: 10.1590/0102-311xen131422
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution from forest burning as environmental risk for millions of inhabitants of the Brazilian Amazon: an exposure indicator for human health

Abstract: In this study, we propose an indicator of air pollution exposure to identify potential hazardous areas for human health in the Amazon and Central-West Regions of Brazil from 2010 to 2019. This indicator aggregates both concentrations and time of exposure to fine particulate matter (PM2.5), according to the current limit recommended by the World Health Organization (WHO). We used daily PM2.5 averages obtained from the Brazilian Health Integrated Environmental Information System (SISAM) to calculate the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The state of Amazonas, traditionally regarded as the most preserved within the Legal Amazon, has recently undergone substantial changes in land use due to intense human occupation, resulting in significant aerosol particle emissions, primarily attributed to biomass burning [ 45 , 46 , 47 , 48 ]. A study conducted over a decade ago (2002 to 2009) revealed relatively low concentrations of fine particulate matter [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The state of Amazonas, traditionally regarded as the most preserved within the Legal Amazon, has recently undergone substantial changes in land use due to intense human occupation, resulting in significant aerosol particle emissions, primarily attributed to biomass burning [ 45 , 46 , 47 , 48 ]. A study conducted over a decade ago (2002 to 2009) revealed relatively low concentrations of fine particulate matter [ 49 ].…”
Section: Discussionmentioning
confidence: 99%